2001
DOI: 10.1128/aac.45.3.825-836.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Properties of Ro 63-9141, a Novel Broad-Spectrum Cephalosporin with Activity against Methicillin-Resistant Staphylococci

Abstract: Ro 63-9141 is a new member of the pyrrolidinone-3-ylidenemethyl cephem series of cephalosporins. Its antibacterial spectrum was evaluated against significant gram-positive and gram-negative pathogens in comparison with those of reference drugs, including cefotaxime, cefepime, meropenem, and ciprofloxacin. Ro 63-9141 showed high antibacterial in vitro activity against gram-positive bacteria except ampicillin-resistant enterococci, particularly vancomycin-resistant strains of Enterococcus faecium. Its MIC at whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
236
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(264 citation statements)
references
References 18 publications
26
236
1
1
Order By: Relevance
“…Interactions with cephalosporin side chains occurs in the groove, closed in the free PBP 2a enzyme, binds to the 7-acyl amino side chain, and in another extended groove where it interacts with the 3'-cephem side chain through noncovalent interactions (Lim & Strynadka 2002). It is stable to class A penicillinases produced by S. aureus and enteric gram-negative microorganisms and is more stable to few class C beta-lactamases of enteric gram-negative microorganisms (Hebeisen et al, 2001). …”
Section: Fifth Generation Cephalosporinsmentioning
confidence: 99%
“…Interactions with cephalosporin side chains occurs in the groove, closed in the free PBP 2a enzyme, binds to the 7-acyl amino side chain, and in another extended groove where it interacts with the 3'-cephem side chain through noncovalent interactions (Lim & Strynadka 2002). It is stable to class A penicillinases produced by S. aureus and enteric gram-negative microorganisms and is more stable to few class C beta-lactamases of enteric gram-negative microorganisms (Hebeisen et al, 2001). …”
Section: Fifth Generation Cephalosporinsmentioning
confidence: 99%
“…It has been shown that ceftobiprole was highly active against penicillin-susceptible isolates of S. pneumoniae (MIC 90 , 0.03 µg/mL). 15 Ceftobiprole was active against 299 drug-susceptible and -resistant pneumococci, with MIC 50 and MIC 90 values of 0.016 and 0.016 µg/mL (penicillin-susceptible isolates), 0.06 and 0.5 µg/mL (penicillin-intermediate isolates) and 0.5 and 1.0 µg/mL (penicillin-resistant isolates), respectively. 29 Ceftobiprole MICs against S. pneumoniae were lower than those of ceftriaxone and cefuroxime in two worldwide surveillance studies.…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…5,[10][11][12][13][14] Ceftobiprole is not active against extended-spectrum beta-lactamase (ESBL) producing strains of Enterobacteriaceae. 13,15,16 Published MIC data for a range of microorganisms are shown in Table 1.…”
Section: In Vitro Antibacterial Activity: Ceftobiprole and The Penicimentioning
confidence: 99%
See 2 more Smart Citations